OPTIMASI CLASH DETECTION DENGAN PENDEKATAN BUILDING INFORMATION MODELING PADA GEDUNG BERTINGKAT: STUDI KASUS GEDUNG KANTOR SARANA DAN PRASARANA DIREKTORAT JENDERAL BEA DAN CUKAI DI BANJARMASIN - Perdana, Kevin Putra; Purnamasari, Eka; Fathurrahman, Fathurrahman (INFO-TEKNIK, 2023)
This research explores the application of Building Information Modeling (BIM) for collision detection in multi-story buildings, with a focus on the Directorate General of Customs and Excise's Office of Facilities and Infrastructure in Banjarmasin as a case study. The primary objectives of this research are to quantify and analyze collisions among structural, architectural, and MEP (Mechanical, Electrical, and Plumbing) elements within the building, and to assess how collision detection impacts material quantities and cost estimates. The study leveraged Revit 2022 to construct a comprehensive 3D building model and utilized Navisworks 2022 for clash detection analysis, identifying clashes across the three mentioned components. Subsequently, clash resolution strategies, including component geometry and position adjustments, were employed. The investigation reveals that design errors emerged as the predominant cause of collisions, followed closely by design inconsistencies and mismatches. The findings underscore the potential for substantial cost savings, up to 10.056% of the total project budget, primarily driven by optimizations in architectural materials. As a result, the study recommends a renewed emphasis on design coordination as a means to proactively prevent clashes and thereby reduce overall project costs.